"Psyche" : Aristotle on remote sensing touch and human cognitive enhancement - Bonda, Eva (Ex-libris, n°1, 2018)
In this Monograph, Eva Bonda proposes a new theory of the sense of ‘touch’ in Aristotle’s foundational treatise ‘Περὶ Ψυχῆς’ (On the Soul). The author argues that a delve into the aristoteleian lexicon reveals an intrinsically dialectical theory of the senses, that of all senses being reduced to ‘touch’ either as an experience of polysensoriality or synaeshthesia or of remote sensing touch. ‘Touch’ becomes in Aristotle the thread connecting the matter to its transmutation into the abstract mind. On the basis of neuroimaging results, Eva Bonda describes how the human brain codes, as intangible cognitive phenomena, the body image and the memory through touch. The Monograph is based in Author’s participation at the 2016 World Conference ‘Aristotle 2400 years from his birth’, organized by Aristotle University of Thessaloniki in Greece on 23-28 May 2016. The Congress, in celebration of the 2400th anniversary from Aristotle’s birth, was held in ancient Stageira, the birthplace of Aristotle (born c. 384 BCE) and in ancient Mieza, the place where Aristotle taught Alexander the Great. Dr Eva Bonda has expertise in Cognitive Neuroscience and Neuroimaging, Primate Neuroanatomy, and Clinical Psychotherapy. She studied and conducted research at McGill University in Canada, Université Pierre & Marie Curie in Paris, University of California at Davis and Washington University in Saint-Louis in USA, and at Psychology UCL and Crystallography Birkbeck College, University of London, UK. She pioneered neuroimaging experiments in the human brain. 21 color illustrations.